Academic Affiliation and Surgical Volume Predict Survival in Head and Neck Cancer Patients Receiving Surgery. (25th May 2020) - Farquhar, Douglas R.; Masood, Maheer M.; Lenze, Nicholas R.; Sheth, Siddharth; Patel, Samip N.; Lumley, Catherine; Zanation, Adam M.; Weissler, Mark C.; Olshan, Andrew F.; Hackman, Trevor G.
Abstract : Objective: To determine whether the academic affiliation or surgical volume affects the overall survival (OS) of human papillomavirus (HPV)–negative head and neck squamous cell carcinoma (HNSCC) patients receiving surgery. Methods: A retrospective study of 39 North Carolina Medical Centers was conducted. Treatment centers were classified as academic hospitals, community cancer centers, or community hospitals and were divided into thirds by volume. The primary outcome was 5‐year OS. Hazard ratios (HR) were determined using Cox proportional hazard models, adjusting for demographics, tumor site, stage, insurance status, tobacco use, alcohol use, stage, chemotherapy, and radiation therapy. Patients were also stratified by stage (early stage and advanced stage). Results: Patients treated at community cancer centers had significantly better 5‐year OS (HR 0.68, 95% confidence interval [CI] = 0.48–0.98), and patients treated at academic hospitals trended toward better 5‐year OS (HR 0.72, 95% CI = 0.50–1.04) compared to patients treated at community hospitals. The effect for academic affiliation on survival was more pronounced for patients with advanced stage cancer at diagnosis (HR 0.60, 95% CI = 0.37–0.95). There were no significant survival differences among early stage patients by treatment center type. Top‐third (HR = 0.64, 95% CI = 0.42–0.96) centers by surgical volume had significantly better 5‐year OS, and middle‐third (HR = 0.71, 95% CI = 0.51–1.03) centers by volume trended toward better 5‐year OS when compared to the bottom‐third centers by volume. Conclusion: Patients treated at academic hospitals, community cancer centers, and hospitals in the top third by case volume have favorable survival for HPV‐negative HNSCC. The effect for academic hospitals is most pronounced among advanced stage patients. Level of Evidence: 4 Laryngoscope, 131:E479–E488, 2021